Возрастный аспект оценки фондов научной литературы - Вяльяотс, М.В. (Knygotyra, 1974)
The rather complicated problem to determine criteria of evaluating the effectiveness of library activities has not as yet been sufficiently studied. As one of the most important indicators, enabling to appraise standards of library activities and the correspondence of the book stacks to demands of the readers, the book circulation index is regarded. But the methodology used in calculating this index does not take into consideration the aging aspect of the scientific literature. On the grounds of a study of literature on theory of science and of experiments zased on bibliographic indices (Kнижнaя лeтопись) and on analysis of some research serials and library stacks of some research serials and library stacks of the Estonian Academy of Science, the author of this paper discloses the aging process of scientific literature, i.e. the diminishing intensity of its use. Certain coefficients are deduced. The use of these coefficients may be helpful not only in appraising the circulation data of the scientific literature but also eliminating from stacks literature, which lost its scientific value, transferring this literature to depositary libraries and thus creating prospects of a more rational and intensive use of library resources.